Pengaruh Kinerja Karyawan Terhadap Kualitas SDM Dan Organisasi - Nona Ratu Syifa Putri; Chudri Ariq Zulqarnain; Muhammad Farhan (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Employee work has an influence on the quality of human resources and the Organization. This is because if Employee Performance is improved, the quality of their human resources will increase. However, if Employee Performance decreases, it will certainly make the quality of their human resources decrease. As well as stereotypes of theories that have been widespread regarding Employee Performance, namely, Organizations with high levels of performance certainly come from qualified human resources. So, it will quickly make an Organization able to achieve its goals. Therefore, the discussion related to the correlation between Employee Performance and the Quality of Human Resources and Organizations will be discussed further.